Answer:
Please see attached image
Explanation:
We can work on the products of binomials using distributive property to multiply every term of the first binomial by every term of the second one. Finally combine like terms to get the trinomial that results:
1)
![(2+a)(2+a)=4+2a+2a+a^2=4+4a+a^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gi2whkjgil19q2dzftk4pxctstcyfahd12.png)
2)
![(2a+1)(2a+1)=4a^2+2a+2a+1=4a^2+4a+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5eietxerms3uoflqphed6fstf91mgfb8ox.png)
3)
![(2a-1)(2a-1)=4a^2-2a-2a+1=4a^2-4a+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dmjkwpwm93olhn3vci23jnlkw0iz2aaqj6.png)
4)
![(2-a)(2-a)=4-2a-2a+a^2=4-4a+a^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gnwijxq5hyzq8vzletu34bfm03szybz28j.png)